2022
DOI: 10.1590/0001-3765202220210540
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular hydrolytic enzymes produced by yeasts from Antarctic lichens

Abstract: In the Antarctic environment, yeasts are versatile eukaryotes that have shown wide dispersion in different substrates, producing active enzymes in extreme conditions, but their relevance in biotechnological applications is largely unknown. The aim of this study was to evaluate the production of extracellular hydrolases by yeasts isolated from Antarctic lichens and molecularly identify these isolates. From a total of 144 isolates on the screening, 109 (76%) produced at least one of the hydrolases tested, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Among the 97 genera reported, saprophytes were dominant in all sampling sites, followed by those considered to be symbionts and pathogens of plants and animals. Our results are consistent with recent fungal metabarcoding studies in different Antarctic environments [16, 36–38, 56, 57, 65–67]. Schütte et al [68] and Gonçalves et al [40] suggested that a proportion of the kingdom Fungi can colonize the cold environments of the polar regions, where they degrade organic matter at low temperatures, producing organic breakdown products and making these available to other organisms in the trophic web.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the 97 genera reported, saprophytes were dominant in all sampling sites, followed by those considered to be symbionts and pathogens of plants and animals. Our results are consistent with recent fungal metabarcoding studies in different Antarctic environments [16, 36–38, 56, 57, 65–67]. Schütte et al [68] and Gonçalves et al [40] suggested that a proportion of the kingdom Fungi can colonize the cold environments of the polar regions, where they degrade organic matter at low temperatures, producing organic breakdown products and making these available to other organisms in the trophic web.…”
Section: Discussionsupporting
confidence: 93%
“…Leucosporidium includes yeasts commonly inhabiting low-temperature environments of polar and temperate regions [62]. In Antarctica, Leucosporidum taxa have been detected, mainly in traditional culturing studies, in seawater [60] and associated with the plant Colobanthus quitensis [59] and lichen thalli [65] in maritime Antarctica.…”
Section: Discussionmentioning
confidence: 99%